Senior love triangle - Kosofsky, Isadora (Kehrer, 2019)
Photographed in Los Angeles, 'Senior Love Triangle' documents three senior citizens in a romantic conflict. Jeanie, age 81, and Adina, age 90, share William, age 84, as a partner and companion, often all spending time together. In his late 70s, Will formed a relationship with Adina. Then, Will moved into another retirement home where he fell in love with Jeanie. Since Will did not want to choose between Jeanie and Adina, they formed a trio. While pushing against sociocultural norms about senior citizens, the connection between Jeanie, Will and Adina also reveals ageless needs, anxieties and contradictions. Renowned documentary photographer Isadora Kosofsky met Jeanie, Will and Adina when she was 17, chronicling their moments of adventure, desire and loneliness with an empathetic gaze for years.00Exhibition: Photoville Los Angeles, USA (26.04. - 28.04.2019 & 02.05. - 05.05.2019).